Religião e política no Brasil : análise discursiva de comentários online de eleitores no pleito presidencial de 2010 - Magalhães, Amarildo Pinheiro (2016)
Politics and religion have always been intertwined in Brazilian history. Current research forwards the religious elements in the 2010 presidential elections in Brazil in the wake of production conditions. How may one explain that, within a laical State and an increase in the number of people who declare themselves unbelievers, religious factors determine the formulation of discourses and political-electoral practices in Brazil? The question triggers an analysis through identification processes, on the function of Christian religious discourse in the formation and dissemination of discourses by Brazilian voters with regard to choices of candidates in the Internet during the 2010 elections. Possible responses to the issue is foregrounded theoretical and methodologically on Discourse Analysis (DA), French mode, based on studies by Michel Pêcheux and on contributions by other French and Brazilian researchers on DA and communication fields devoted to the Brazilian referential. Material was restricted to commentaries by voters on the Orket site and on the official site of candidate for the Workers´ Party, Dilma Rousseff, the main target of religious comments. Analysis revealed that the voters, who were also the authors of the commentaries, were dominated by the subject-form of the right, or rather, the subject-form dominated by the State which replaced God in the transition from feudal to capitalist production. Several factors, however, underscore that identification is not done fully, In other words, the subject does not function integrally in these discourses. There are factors that pass through the process whose origin lies in discursive formations which are foreign to the corresponding knowledge of the subject-form. It may be supposed that the process is explained by the functioning of religiosity as a characteristic of the so-called national identity, or rather, being a citizen of a Christian country is a fact associated with the imaginary of Brazil-ness so that any and every action involving decision on the nation´s fate has to pass through the Christian religiosity stance associated to Brazil-ness. Within the Brazilian situation, the laical condition of the bourgeois State is supplanted by Christianity as a founding discourse. In spite of the juridical factors involved, something speaks through the imaginary and the unconscious to Brazilian citizens and convinces them that the Christian factors should not be discarded when the fate of the nation is being decided. It is the permeability of the religious in what should be laical and impairs any form of total protection.